S-Phase Cell Cycle Arrest, Apoptosis, and Molecular Mechanisms of Aplasia Ras homolog Member I–Induced Human Ovarian Cancer SKOV3 Cell Lines. Issue 4 (1st May 2014) - Zhu, Qiaoying; Hu, Jianming; Meng, Huijuan; Shen, Yufei; Zhou, Jinhua; Zhu, Zhihong
Abstract : Objective: Aplasia Ras homolog member I ( ARHI ) is associated with human ovarian cancer (HOC) growth and proliferation; however, the mechanisms are unclear. The purpose of this study was to investigate ARHI effects in HOC SKOV3 cells. Methods: We transfected SKOV3 cells with PIRES2-EGFP-ARHI and measured growth inhibition rates, cell cycle distribution, apoptosis rates, and expression of P-STAT3 (phosphorylated signal transduction and activators of transcription 3) and P-ERK (phosphorylated extracellular signal regulated protein kinase). Results: Our data showed significant inhibition of growth, significantly increased S-phase arrest and apoptosis rates, and reduction of P-STAT3 and P-ERK1/2 expression levels. Conclusions: We propose the mechanism may involve ARHI- induced phosphorylation of ERK1/2 and STAT3 protein kinases, thereby blocking proliferation signaling pathways, to induce HOC SKOV3 apoptosis.